Nutritional Status and Gastrointestinal Symptoms in Oncology Patients Receiving Chemotherapy - Casari, Larissa (2021)
Introduction: The nutritional status of oncologic patients varies greatly throughout the disease, further to gastrointestinal tract related adverse effects that are common during chemotherapy treatment. Objective: Evaluate the nutritional status and the presence of gastrointestinal symptoms in oncologic patients undergoing chemotherapy. Method: Cross-sectional study with patients in treatment in the Chemotherapy Unit of the Hospital School of Pelotas Federal University (UFPel), RS, from April to July 2019. Sociodemographic data and questions related to the disease were obtained through a questionnaire. To assess the nutritional status and gastrointestinal symptoms the Patient-Generated Subjective Global Assessment was utilized. Data analysis was performed through descriptive analysis, and the association between categorical variables was verified by Pearson’s chi-square test (p<0.05). Results: A total of one hundred one patients was evaluated, mean age of 58.6 years, with higher prevalence of females (58.4%), Caucasian (77.2%), married (53.0%), belonging to class C (50.4%). Higher prevalence of gastrointestinal tract (34.6%) and breast (27.8%) cancer was found. Most patients were classified as well-nourished (66.3%), while early satiety (56.0%), xerostomia (54.0%), loss of apetite (42.0%), and nausea (37.0%) were the symptoms most cited. No statistical association was encountered between nutritional status and any of the gastrointestinal symptoms. Conclusion: The nutritional status of most patients was classified as well nourished, but attention is needed for the occurrence of gastrointestinal symptoms.